Food Business Opportunities in ASEAN: Responding to Rising Demand from a Growing Population - Wahyu Adhi Saputro; Octaviana Helbawanti; Ulfah Nurdiani; Fitri Amalinda Harahap; Amalia Nadifta Ulfa (Universitas Panji Sakti, 2026)
Population growth occurs every year in ASEAN countries. This research aims to determine food business opportunities in response to rising food demand in the increasing population of ASEAN countries. Descriptive methods were used in this research with secondary data from 2017 to 2021. Secondary data came from relevant sources, namely the Global Food Security Index and several others. The data analysis used in this research is contribution analysis and forecasting population growth rates using a logarithmic model. Contribution analysis is obtained by dividing the population of each country in ASEAN (people) by the total population of ASEAN or the world. Meanwhile, the logarithmic growth rate is calculated using this model, assuming that at a certain point in time, the population will approach an equilibrium point. The results of the study show that the population growth rate in most ASEAN countries is at a positive level. With the highest level in Cambodia at 1.6%, followed by the Philippines at 1.4% and Laos at 1.1%. The largest contribution to the population in ASEAN countries is Indonesia, with 40.87 percent. Based on the research results, it was also found that the development of the GFSI value was the highest for Singapore, with an achievement of 83.21. The existence of a growing population creates opportunities for countries with abundant natural resources. This potential exists to fulfil food requirements for countries where food production faces domestic difficulties. Each country can try to maintain its staple food reserves in accordance with the population growth rate so as not to experience food shortages.